Adobe Photoshop classroom in a book 2020 release : the official training workbook from Adobe - Faulkner, Andrew; Chavez, Conrad (Classroom in a book., 2020)
Creative professionals seeking the fastest, easiest, most comprehensive way to learn Adobe Photoshop choose Adobe Photoshop Classroom in a Book (2020 release) from Adobe Press. The 15 project-based lessons show key step-by-step techniques for working in Photoshop, including how to correct, enhance, and distort digital images, create image composites, and prepare images for print and the web. In addition to learning the essential elements of the Photoshop interface, this revised edition for the 2020 release covers features like the new Object Selection tool, saving Cloud Documents for easy access from Photoshop on other devices such as the Apple iPad, removing objects with upgraded Content-Aware Fill, applying styles and objects such as gradients and shapes, instantly using redesigned Presets panels, and much more! The online companion files include all the necessary assets for readers to complete the projects featured in each chapter. All buyers of the book get full access to the Web Edition: A Web-based version of the complete ebook enhanced with video and multiple-choice quizzes.